225k views
5 votes
Solve the system of equation
2x-y= 6
x+y= -3

2 Answers

3 votes

Answer:

(1, - 4 )

Explanation:

Given the 2 equations

2x - y = 6 → (1)

x + y = - 3 → (2)

Adding the equations term by term will eliminate the term in y, that is

3x = 3 ( divide both sides by 3 )

x = 1

Substitute x = 1 into either of the 2 equations and solve for y

Substituting in (2) gives

1 + y = - 3 ( subtract 1 from both sides )

y = - 4

Solution is (1, - 4 )

User Reduckted
by
5.6k points
3 votes

that is the solution to the simultaneous equation

Solve the system of equation 2x-y= 6 x+y= -3-example-1
User Cmancre
by
5.2k points